Mindfulness-induced selflessness: a MEG neurophenomenological study - Dor-Ziderman, Yair; Berkovich-Ohana, Aviva; Glicksohn, Joseph; Goldstein, Abraham (Frontiers in Human Neuroscience, 2013)
Contemporary philosophical and neurocognitive studies of the self have dissociated two distinct types of self-awareness: a 'narrative' self-awareness (NS) weaving together episodic memory, future planning and self-evaluation into a coherent self-narrative and identity, and a 'minimal' self-awareness (MS) focused on present momentary experience and closely tied to the sense of agency and ownership. Long-term Buddhist meditation practice aims at realization of a 'selfless' mode of awareness (SL), where identification with a static sense of self is replaced by identification with the phenomenon of experiencing itself. NS-mediating mechanisms have been explored by neuroimaging, mainly fMRI, implicating prefrontal midline structures, but MS processes are not well characterized and SL even less so. To this end we tested 12 long-term mindfulness meditators using a neurophenomenological study design, incorporating both magnetoencephalogram (MEG) recordings and first person descriptions. We found that (1) NS attenuation involves extensive frontal, and medial prefrontal gamma band (60-80 Hz) power decreases, consistent with fMRI and intracranial EEG findings; (2) MS attenuation is related to beta-band (13-25 Hz) power decreases in a network that includes ventral medial prefrontal, medial posterior and lateral parietal regions; and (3) the experience of selflessness is linked to attenuation of beta-band activity in the right inferior parietal lobule. These results highlight the role of dissociable frequency-dependent networks in supporting different modes of self-processing, and the utility of combining phenomenology, mindfulness training and electrophysiological neuroimaging for characterizing self-awareness.